(untitled) (Research, Society and Development, 2020)
Objective: to know the perceptions of homeless people about their human rights to health. Method: qualitative, exploratory-descriptive study conducted during 2015 and 2016 through participant observation, registered on a field diary, and semi-structured interviews with four privileged interlocutors. The analyzes were carried out according to the steps of the thematic analysis, three main themes were identified: the perceptions about human rights to health and society; the perceptions about human rights to health and public policies and the perceptions about human rights to health and social stigmas. Results: There is an invisibility of the rights of homeless people, they are not recognized as subjects of law and health. Also, it was observed directly linked to need active participation in social movements to know their rights. Public policies are constructed out of context of the countless demands from homeless people, and the state and society must guarantee the right to a dignified life, facing the exclusion and invisibility of this situation. Bureaucracy appears to be ineffective in enabling a more dignified life, access to health and rights guarantee. The stigma and judgement of homeless people appears naturalized, that is being someone socially wrong, which contributes to the lack of recognition as a subject of rights. Conclusions: in order to think about health, there is indeed to understand its relations with human rights, expanding its view on citizenship, society, health system, social assistance, the images of the homeless population and their social stigmas.